Judicial review of the pre-trial criminal proceedings as a form of the implementation of the judiciary (Journal of actual problems of jurisprudence, 2019)
The article deals with controversial issues determining the place of judicial review of pre-trial proceedingsin the judicial power in the light of the functions and modalities of the judiciary.Concluded that the judicialcontrol of the pre-trial proceedings – is a form of implementation of the judicial power.Keywords: Criminal trial, the judiciary, justice, judiciary, judicial control.